Benefits and harms of replacement therapy with Alpha 1 Antitrypsin in patients with documented enzyme deficiency and Chronic Obstructive Pulmonary Disease: A systematic review and network meta-analysis (2021)
ABSTRACT TITLE: Benefits and harms of replacement therapy with Alpha 1 Antitrypsin in patients with documented enzyme deficiency and Chronic Obstructive Pulmonary Disease: A systematic review and network meta-analysis. OBJECTIVE: To identify the available scientific evidence regarding the benefits and safety of replacement therapy with Alpha 1-Antitrypsin compared with endobronchial or surgical management for reduction of lung volume, lung transplantation, standard of care for chronic obstructive pulmonary disease, and placebo or control/no treatment in patients with documented enzyme deficiency, presenting with chronic obstructive pulmonary disease. METHODS: A systematic review and meta-analysis was conducted. MEDLINE-PubMed (via Ovid), EMBASE (via Elsevier), LILACS and the Cochrane Library of Controlled Register of Trials (CENTRAL) were assessed for randomized controlled trials (RCT); cluster, factorial, parallel-design and cross-over designs were included, from inception to May of 2021. Any restrictions regarding language, setting, report status or date of publication were included. Non-published articles in clinicaltrials.gov, and grey literature in ProQuest were also considered. Trials studying adult patients with documented Alpha-1 Antitrypsin Deficiency (A1AD) and diagnosed with Chronic Obstructive Pulmonary Disease (COPD), treated with A1A augmentation therapy or other standard care interventions (according to current guidelines for COPD treatment1) such as inhaled corticosteroids, phosphodiesterase 4 inhibitors, antibiotics, inhaled anticholinergic or beta 2 agents, anti-oxidant, lung volume reduction interventions or lung transplant were included. Patient important outcomes as well as surrogate outcomes were assessed. Risk of bias (ROB) for each included trial was independently assessed, using the Cochrane Risk of Bias tool (ROB2). DerSimonian-Laird random-effects models for all pairwise comparisons were used. Heterogeneity was calculated with Q statistic